Learning Using Google Classroom Can Improve Learning Outcomes for Students of State Vocational High School 9 Samarinda City - Jumini, Jumini (PT Literasi Nusantara Publisher, 2023)
This study aims to describe the increase in results aiming to find out whether Google Classroom media can improve student learning outcomes. This research is a type of quantitative research and the technique used in this research is a simple random sampling technique. The data collection technique is an objective test in the form of the practice of writing commercial letters before and after using Google Classroom. The type of research is Pre-Experimental Design with the type One Group Pre-test Post-test Design. There is a pre-test before being given treatment, and a post-test, which is done in order to be able to compare with the conditions before and after being given treatment. These results indicate that making commercial letters in the business field by paying attention to content, systematics, and sentences for 36 students State Vocational High School 9 Samarinda is known to have an average score of 85.11 student learning outcomes, up 8.28. From the completeness presentation from 78.53%, it rose to 86.65% compared to before using Google Classroom. Study completeness with online learning using Google Classroom was 86.65%, an increase of 8.12% compared to learning completeness before using Google Classroom in the previous KD which reached 78.53%.